Nanomedicine: Transforming the Management of Ocular Neuroinflammatory and Neurodegenerative Diseases - Georgia Savvidou; Ellas Spyratou; Maria-Eleni Zachou; Efstathios P. Efstathopoulos (Journal of Nanotheranostics)
Nanomedicine is emerging as a groundbreaking strategy for the management of the neuro-visual symptoms of neuroinflammatory and neurodegenerative diseases. This innovative field of study leverages nanoscale materials and technologies to improve drug delivery, enabling targeted treatments to reach the affected ocular tissues. By facilitating the transport of therapeutic agents across the blood–retinal barrier and boosting their bioavailability, nanomedicine holds the potential to significantly mitigate the symptoms of conditions such as Alzheimer’s disease (AD), Parkinson’s disease (PD), multiple sclerosis (MS), etc. This review summarizes the latest developments in nanomedicine applications for the management of these ocular conditions, highlighting their capacity to foster more effective disease diagnosis and treatment.